Peningkatan Kualitas Hidup pada Pengemudi Angkutan Bahan Berbahaya melalui Psikoedukasi di Bekasi - Hasyim, Farah Fadilah; Hidayat, Novi; Hariyanto, Denny; Dwiwangsa, Arya (Universitas Pahlawan Tuanku Tambusai, 2026)
Drivers of hazardous materials (B3) are a group of workers who face high occupational risks, both in terms of physical safety and mental health. Heavy workloads, long working hours, pressure to maintain safety, and the risk of accidents can have a negative impact on their quality of life. This community service activity aims to increase the understanding of B3 transport drivers regarding the importance of maintaining quality of life, which includes physical, psychological, social, and work environment aspects. The methods used in this activity are educational and participatory approaches through socialisation, interactive discussions, and psychoeducation approaches related to occupational health. The results of the activity show that most participants do not yet fully understand the concept of quality of life as a whole, but they show great enthusiasm for topics such as stress management, work fatigue, and work-life balance. This programme is expected to serve as an example of a sustainable community service activity in supporting the occupational safety and welfare of B3 transport drivers.